Accidental Use of Milk With an Increased Concentration of Aflatoxins Causes Significant DNA Damage in Hospital Workers Exposed to Ionizing Radiation - Mrdjanovic, Jasminka; Sudji, Jan; Srdjenovic, Branislava; Dojcinovic, Sanja; Bogdanovic, Visnja; Jakovljevic, Dea Karaba; Jurisic, Vladimir (Frontiers in Public Health, 2020)
The occupational exposure to ionizing radiation (Irad) or associated with mycotoxin-contaminated food may lead to genome damage and contribute to health risk. DNA damage in 80 blood samples of hospital workers occupationally exposed to low—doses of Irad was compared with 80 healthy controls. Among them, 40 participants accidentally consumed milk with increased concentration of Aflatoxin. All participants underwent the testing for micronuclei from blood, and 40 of them 8-OHdG from urine. The frequency of micronuclei (MN) was analyzed by cytokinesis-block peripheral blood lymphocytes and the level of urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) by ELISA. The Irad led to increased frequency of MN (p < 0.05) and 8-OHdG level at exposed hospital workers. The consumption of milk with increased concentration of aflatoxin probably raised MN frequency and 8-OHdG value. Higher consumption of aflatoxin-contaminated milk (≥2 L/monthly) caused significantly increased MN frequency and 8-OHdG value in comparison to lower milk intake (≤0.5 L/monthly). Also, confounding factors, such as age, gender, and smoking status of all participants were included in the study. The obtained results revealed an increased incidence of MN and 8-OHdG level among hospital workers exposed to low-doses of IRad and milk with increased aflatoxin concentration.